2014
DOI: 10.1038/ncomms4357
|View full text |Cite
|
Sign up to set email alerts
|

A two-locus interaction causes interspecific hybrid weakness in rice

Abstract: Reproductive barriers perform a vital role during speciation. Hybrid weakness, the poorer development of hybrids compared with their parents, hinders gene exchange between different species at the postzygotic stage. Here we show that two incompatible dominant loci (Hwi1 and Hwi2) involving three genes are likely to determine the high temperature-dependent expression of hybrid weakness in interspecific hybrids of rice. Hwi1 comprises two leucine-rich repeat receptor-like kinase (LRR–RLK) genes, 25L1 and 25L2, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
125
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(133 citation statements)
references
References 44 publications
2
125
2
1
Order By: Relevance
“…In addition, a chemically induced allele at a gene encoding a cysteine synthase can combine with a natural DM2 allele to cause necrosis (Tahir et al, 2012). Outside of A. thaliana , hybrid necrosis alleles encode a cysteine protease (Krüger et al, 2002), a kinase (Yamamoto et al, 2010) and a subtilisin-like protease (Chen et al, 2014). Enzyme-encoding genes are clearly enriched, but in most cases we do not know yet how they modulate the activity of NLRs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a chemically induced allele at a gene encoding a cysteine synthase can combine with a natural DM2 allele to cause necrosis (Tahir et al, 2012). Outside of A. thaliana , hybrid necrosis alleles encode a cysteine protease (Krüger et al, 2002), a kinase (Yamamoto et al, 2010) and a subtilisin-like protease (Chen et al, 2014). Enzyme-encoding genes are clearly enriched, but in most cases we do not know yet how they modulate the activity of NLRs.…”
Section: Discussionmentioning
confidence: 99%
“…Of the six causal loci that have been positively identified, one encodes an NLR and another one a known NLR-interactor. In addition, the mapping interval for one of the remaining loci includes several NLRs (Chen et al, 2014; Jeuken et al, 2009; Krüger et al, 2002; Yamamoto et al, 2010). Similarly, the first hybrid necrosis gene positively identified in Arabidopsis thaliana , DANGEROUS MIX1 ( DM1 ), encodes an NLR.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it was recently shown that a hybrid lethality allele has risen to high frequency in a population of M. guttatus due to linked selection for an allele that confers copper tolerance (Wright et al 2013). Natural selection is also presumed to play a role in divergence among disease resistance genes that cause hybrid necrosis in Arabidopsis and rice (Kruger et al 2002;Alcazar et al 2009;Jeuken et al 2009;Yamamoto et al 2010;Chen et al 2014), although direct population genetic evidence is lacking. Likewise, the genes that cause cytoplasmic male sterility between Mimulus species (involving the same IM62 and SF lines used in this study) seem more likely to have evolved by selfish mitochondrial evolution and compensatory nuclear coevolution than by genetic drift (Barr and Fishman 2010).…”
Section: Discussionmentioning
confidence: 99%
“…There are also hints that natural selection can contribute to the spread of incompatible alleles within populations and species. For example, plant hybrid necrosis has been mapped repeatedly to disease resistance genes (Krüger et al 2002; Alcazar et al 2009;Jeuken et al 2009;Yamamoto et al 2010;Chen et al 2014), which are likely targets of adaptive divergence to unique pathogen communities (Bomblies and Weigel 2007). Additionally, many hybrid incompatibility genes show molecular signatures of positive selection (Presgraves et al 2003;Brideau et al 2006;Maheshwari et al 2008;Oliver et al 2009;Phadnis and Orr 2009;Tang and Presgraves 2009), but, interestingly, few of these genes seem to be involved in classical ecological adaptation.…”
mentioning
confidence: 99%
“…Recently, Chen et al (2014) identified two incompatible dominant loci, Hwi1 and Hwi2, controlling the hybrid weakness in the interspecific hybrids of rice. These two loci are located on chromosome 11 and 1, respectively.…”
Section: Introductionmentioning
confidence: 99%